"They've Always Been Good Mothers": An Ethnographic Study of Early Childhood Intervention in Dublin. Issue 7 (3rd October 2019) - Maggio, Rodolfo
Abstract : Randomized Controlled Trials are considered the "gold standard" in the evaluation of early childhood intervention (ECI) initiatives. These trials, however, do not illustrate the internal mechanisms of the intervention. Ethnography is better positioned to observe the long-term, intimate relationships among the actors involved and the process of program delivery. Preparing for Life is one of the few ECI initiatives to be studied with a combination of both methodologies. In so doing and looking ethnographically at the "logical model" illustrates how it does not reflect the "good relationship, " which is better explained with a blend of relational theories.